HUBUNGAN PENGETAHUAN DENGAN KETERATURAN PRETANAL YOGA PADA IBU HAMIL TRIMESTER III - Ervin Rufaindah (Media Husada Journal of Midwifery Science, 2024)
Many prenatal yoga classes are now facilitated by programs from Community Health Centers, but there are still many pregnant women who have not taken advantage of prenatal yoga classes because there are still many pregnant women who do not understand the importance of prenatal yoga. The aim of this research is to analyze the relationship between knowledge and the regularity of prenatal yoga in third trimester pregnant women. The method in this research is observational analytic with a cross-sectional approach. The population and sample amounted to 30 respondents using total sampling techniques. Research data was obtained through a questionnaire on the knowledge and regularity of prenatal yoga for third trimester pregnant women, then analyzed using the Chi Square test. The results of statistical tests using chi square showed that knowledge was related to the regularity of prenatal yoga with a P value (p) <(0.05). Conclusions and suggestions: The conclusion of this study is that there is a relationship between knowledge and regularity of prenatal yoga for pregnant women in the third trimester. It is recommended for pregnant women to always increase their knowledge through counseling by midwives and other media so that they can increase the regularity of prenatal yoga so that they can directly feel the benefits of prenatal yoga and can have a healthy and happy pregnancy.